(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Our earth about 71% percent is covered with water. Out of 71% of water, only 3.5% of water is fresh water and the remaining is saline water. Among the fresh water, only 1.2% of fresh water is under usage. Remaining fresh water is in the forms of glaciers & ice caps. Water is a natural resource. It exists in both the forms of surface water & ground water. In our daily life water plays a vital role, as we are using it for drinking, domestic, agriculture, industry etc. Water quality is one of the most severe concerns around the globe. It is a major factor affecting the human health as well as ecological systems. The drinking water should be free from harmful chemicals and micro-organisms. The quality of drinking water and for various purposes is defined by different quality parameters. In this study, to assess the quality of water in pulivendula urban, Kadapa district, Andhra Pradesh (AP), the water samples are collected, tested and analysed for different quality parameters viz pH, Electrical Conductivity (EC), Total Hardness (TH), Cl-, Total Dissolved Solids (TDS), Alkalinity & Fluorides in our laboratory of department of chemistry, JNTUACE Pulivendula. Then the results of each samples quality parameters are analysed, and compared with standard values as per BIS (Bureau of Indian Standards) and Water Quality Index standards regarding drinking. Finally, these results and comparisons are reported.